Alpha-Gal Bound Aptamer and Vancomycin Synergistically Reduce Staphylococcus aureus Infection In Vivo - Matthew K. Doherty; Claire Shaw; Leslie Woods; Bart C. Weimer (Microorganisms, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a pervasive and persistent threat that requires the development of novel therapies or adjuvants for existing ones. Aptamers, small single-stranded oligonucleotides that form 3D structures and can bind to target molecules, provide one possible therapeutic route, especially when presented in combination with current antibiotic applications. BALB/c α-1, 3-galactosyltransferase (−/−) knockout (GTKO) mice were infected with MRSA via tail vein IV and subsequently treated with the αSA31 aptamer (n = 4), vancomycin (n = 12), or αSA31 plus vancomycin (n = 12), with split doses in the morning and evening. The heart, lungs, liver, spleen, and kidneys were harvested upon necropsy for histological and qPCR analysis. All mice treated with αSA31 alone died, whereas 5/12 mice treated with vancomycin alone and 7/12 mice treated with vancomycin plus αSA31 survived the course of the experiment. The treatment of MRSA-infected mice with Vancomycin and an adjuvant aptamer αSA31 reduced disease persistence and dispersion as compared to treatment with either vancomycin SA31 alone, indicating the combination of antibiotic and specifically targeted αSA31 aptamer could be a novel way to control MRSA infection. The data further indicate that aptamers may serve as a potential therapeutic option for other emerging antibiotic resistant pathogens.